The Sage encyclopedia of lifespan human development - Arterberry, Martha E.; Bornstein, Marc H.; Fingerman, Karen L.; Lansford, Jennifer E. (SAGE Publications, 2018)
Lifespan human development is the study of all aspects of biological, physical, cognitive, socioemotional, and contextual development from conception to the end of life. In approximately 800 signed articles by experts from a wide diversity of fields, this volume explores all individual and situational factors related to human development across the lifespan. The Encyclopedia promises to be an authoritative, discipline-defining work for students and researchers seeking to become familiar with various theories and empirical findings about human development broadly construed. Some of the broad thematic areas will include: Adolescence and Emerging Adulthood Aging Behavioral and Developmental Disorders Cognitive Development Community and Culture Early and Middle Childhood Education through the Lifespan Genetics and Biology Gender and Sexuality Life Events Mental Health through the Lifespan Research Methods ...